2021
DOI: 10.4018/joeuc.20211101.oa26
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-Directed Learning and Educational Technology Readiness on Synchronous E-Learning

Abstract: The coronavirus (COVID-19) has had severe global impacts in many aspects of education. Asian countries and regions have been the first responders to move entirely online since the epidemic started. The aim of this paper is two-folded. First, this study investigates the correlations in order to understand the compounded effects on presences in the participating synchronous learning environments. Second, this paper provide empirical evidence and insights for educators on the future trends of learning and instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 78 publications
0
62
0
1
Order By: Relevance
“…We analyzed the USA and subsequent fiscal policy responses by using linear (econometric estimation) and nonlinear (DSGE model). Ours applies a fundamental model as done in Elenev et al (2020) and in several aspects nevertheless more wide-ranging than that in other studies, hence making room to evaluate a varied set of fiscal policies (Chau et al 2021a;Fong et al 2021;Osorio-Saez et al 2021;Yu et al 2022), thus leading us to discover greater differences regarding the multipliers of directed (UI) vs. undirected (lump-sum) handovers. In this study, the researcher reveals that without rich household different characteristics, the cascading effects for direct cash handovers are more than those for indirect ones.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the USA and subsequent fiscal policy responses by using linear (econometric estimation) and nonlinear (DSGE model). Ours applies a fundamental model as done in Elenev et al (2020) and in several aspects nevertheless more wide-ranging than that in other studies, hence making room to evaluate a varied set of fiscal policies (Chau et al 2021a;Fong et al 2021;Osorio-Saez et al 2021;Yu et al 2022), thus leading us to discover greater differences regarding the multipliers of directed (UI) vs. undirected (lump-sum) handovers. In this study, the researcher reveals that without rich household different characteristics, the cascading effects for direct cash handovers are more than those for indirect ones.…”
Section: Introductionmentioning
confidence: 99%
“…With the wider application of “Internet +,” the combination of “Internet +” and the service industry has brought convenience to the masses in terms of life, study, work, etc [ 17 ]. The combination of “Internet +” and the education industry is important in the industry that brings more development space and possibilities, so as to realize the interaction between offline classroom education and online classroom [ 18 ].…”
Section: Exploratory Research Experiments Of Smart Sports Classrooms ...mentioning
confidence: 99%
“…In terms of the exploration of digital self-directed learning, more recent studies have found that there exists the relationship between self-directed learning ability and digital learning ability, and they have further explored learners’ motivation for using digital technology to facilitate learning ( Lai and Wang, 2017 ; Eroglu and Ozbek, 2018 ; Angriani and Nurcahyo, 2019 ; Chau et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%